2023
DOI: 10.1136/bmjopen-2022-069195
|View full text |Cite
|
Sign up to set email alerts
|

Assessing preferences for HIV pre-exposure prophylaxis (PrEP) delivery services via online pharmacies in Kenya: protocol for a discrete choice experiment

Abstract: IntroductionPre-exposure prophylaxis (PrEP) is highly effective at preventing HIV acquisition, but coverage remains low in high prevalence settings. Initiating and continuing PrEP via online pharmacies is a promising strategy to expand PrEP uptake but little is known about user preferences for this strategy. We describe methods for a discrete choice experiment (DCE) to assess preferences for PrEP delivery from an online pharmacy.Methods and analysisThis cross-sectional study is conducted in Nairobi, Kenya, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…This finding is consistent with other studies in sub‐Saharan Africa, which have shown that pharmacies are perceived as more convenient, more private and less stigmatizing than clinics, particularly by men [73–75]. Thus, our study supports the important role of community pharmacies in differentiated HIV care delivery for men in South Africa [76, 77] and in sub‐Saharan Africa more broadly [75, 78, 79].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with other studies in sub‐Saharan Africa, which have shown that pharmacies are perceived as more convenient, more private and less stigmatizing than clinics, particularly by men [73–75]. Thus, our study supports the important role of community pharmacies in differentiated HIV care delivery for men in South Africa [76, 77] and in sub‐Saharan Africa more broadly [75, 78, 79].…”
Section: Discussionsupporting
confidence: 92%
“…While our study was not designed to estimate willingness to pay, it is important to recognize that some participants may be willing to pay more than 1000 Kenyan shillings (∼ 7 USD as of 2023 when the study was conducted) for the service. A 2023 Kenyan study investigating preferences for online PrEP delivery found that 50% and 25% of adults were willing to pay up to 1000 and 1975 Kenyan shillings, respectively [43]. Future research should explore the willingness to pay for pharmacybased HIV prevention services during pregnancy, pharmacy delivery costs and their impact on service fees, and the potential of cost-sharing strategies for implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HIVST was preferred over RDT in the SEARCH trial, with the majority (71%) of participants in the intervention arm selecting this testing option [46]. A discrete choice experiment evaluating user preferences for PrEP service delivery through online pharmacies in Kenya also found that participants strongly preferred HIVST over RDT [47]. The greater privacy offered by HIVST may overcome barriers associated with RDT, including confidentiality and stigma concerns [48], and increase PrEP coverage among populations that could benefit.…”
Section: Discussionmentioning
confidence: 99%